First person - Andreia Nunes (The Company of Biologists, 2021)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Andreia Nunes is first author on ' Identification of candidate miRNA biomarkers for facioscapulohumeral muscular dystrophy using DUX4-based mouse models', published in DMM. Andreia is a postdoc in the lab of Peter L. Jones at the University of Nevada, Reno School of Medicine, Reno, NV, USA, investigating therapeutics for and disease mechanisms of facioscapulohumeral muscular dystrophy.